BLOCKCHAIN TECHNOLOGY AND SUSTAINABLE PERFORMANCE: THE ROLE OF MANAGEMENT ACCOUNTING SYSTEMS AND DIGITAL TRANSFORMATION IN ASEAN-6 - Muhammad Rizal Satria; Mubassiran Mubassiran (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2026)
Despite the increasing adoption of blockchain technology in organizations, empirical research elucidating the role of blockchain technology in enhancing sustainable performance is currently scant, especially within the context of emerging economies. This investigation seeks to analyze the structural frameworks through which blockchain technology impacts sustainable performance will be analyzed by exploring the mediating function of management accounting systems alongside the moderating influence of digital transformation in ASEAN-6 firms. Data were collected from 230 managerial and accounting professionals in digital-intensive firms across six ASEAN countries using a structured questionnaire. The proposed hypotheses were tested using partial least squares structural equation modeling (PLS-SEM) with mediation and moderation analysis. The results show that blockchain technology significantly enhances sustainable performance through management accounting systems, indicating a significant partial mediation effect. However, digital transformation does not substantially influence the correlation between management accounting systems and sustainable performance. These findings contribute to the literature by validating a moderated mediation framework linking blockchain technology, management accounting frameworks, and sustainable organizational performance in a multi-country ASEAN context. Practically, the results suggest that organizations should complement blockchain adoption with strong management accounting systems to effectively leverage blockchain-generated information for sustainability-oriented decision-making.